Impact of ethnicity on the relevance of the Alcohol Use Disorders Identification Test (AUDIT) in Nepal - Susmita Pandey (BJPsych International)
The Alcohol Use Disorders Identification Test (AUDIT) is a ten-item standardised questionnaire to assess an individual's vulnerability to alcohol use disorders. Three of these ten questions are related to alcohol consumption. Nepal has a distinct alcohol culture, where alcohol use is socially and religiously acceptable in some caste/ethnic groups and is prohibited in others, thereby influencing the scores of AUDIT questions related to all three conceptual domains. Identifying and endorsing subsets of AUDIT questions relevant to different ethnic groups could be the way forward for effective screening of alcohol use disorders in Nepal.